Integrating Ibn Miskawaih’s Akhlak Philosophy Into Public Accountant Ethics: A Framework for Fraud Prevention - Sahla, Widya Ais; Latif, Dwianto Mukhtar (Journal of Social Work and Science Education, 2024)
This study aims to formulate an alternative approach to fraud prevention by internalizing the ethical philosophy of Ibn Miskawaih into the professional behavior of accountants. The study is motivated by the continuing occurrence of fraud involving accountants, which indicates that existing ethical codes have not been fully effective in preventing unethical practices. This research uses a qualitative library method by reviewing relevant literature on Islamic moral philosophy, particularly the concept of akhlak, and relating it to the Basic Principles of Public Accountant Ethics. The results show that the integration of four core virtues, namely self restraint (al iffah), moral courage (as syaja’ah), wisdom (al hikmah), and justice (al ‘adalah), can strengthen ethical attitudes from within the individual. The novelty of this study lies in offering a philosophical and culturally grounded framework that complements existing ethical guidelines. This conceptual contribution provides a foundation for promoting value based ethical awareness in the accounting profession as a strategy for sustainable fraud prevention.